Real Disinvestments and the Distress Anomaly: Evidence from Stocks, Bonds, and Loans - Yang, Shuwen; Aretz, Kevin; Zhang, Yafei (Journal of Financial and Quantitative Analysis, 2026)
Abstract We argue that firms’ ability to disinvest real assets helps rationalize the negative distress premiums in stocks, bonds, and, as we show, loans and firm assets. Using a real options model in which shareholders and debtholders share disinvestment proceeds, the model suggests that the stock (debt) distress premium becomes more negative with the proceeds paid out to that class, and that both premiums can be negative when debtholders receive most of the proceeds. Using hard-asset disinvestment-ability proxies, the stock (bond or loan) distress premium becomes less (more) negative with those proxies, possibly suggesting that shareholders benefit more strongly from nonsecured-asset disinvestments.